Location-allocation models for casualty response planning during catastrophic health events - Caunhye, Aakil M (2014)
Catastrophic health events are natural or man-made incidents that result in casualty numbers that overwhelm the immediate response capabilities of healthcare systems. These events overpower hospitals even when the latter trigger contingency capacity surges that are usually sufficient to deal with regular disasters. We seek to build effective location-allocation plans for the overwhelming number of casualties expected in these events by using alternative care facilities to address surge capacity issues and incorporating triage and the movement of self-evacuees for effective treatment allocation.